Association of FGA, ITGA2, PAI-1 gene polymorphisms with pulmonary embolism - N. M. Kryuchkova; S. Yu. Nikulina; A. A. Chernova; V. N. Maksimov (Российский кардиологический журнал)
Aim. To study of the relationship between gene polymorphisms (FGA, ITGA2, PAI1) and pulmonary embolism (PE).Material and methods. We examined 120 patients with pulmonary embolism, who made up the main group (mean age, 63,22±3,16 years). There were 66 men (mean age, 60,24±3,17 years) and 54 women (mean age, 6,19±3,67 years). The control group consisted of 200 people (mean age, 64,92±3,50 years). The DNA Bank of the Research Institute of Internal and Preventive Medicine was formed during a series of population screenings. All patients signed written informed consent to participate in the molecular genetic study. The work involved the calculation of the following output data: standard deviation; mean square; Pearson chi-squared test; likelihood ratio; Fisher's exact test and linear relationship.Results. The probability of PE among women carriers of ID genotype of FGA gene rs35496957 polymorphism in the group with PE is 2,08 times higher than that in the control group (95% confidence interval (CI), 1,06-4,09; p=0,32); among women carriers of the TT genotype of ITGA2 gene rs1126643 polymorphism in the group with PE — 3,08 times compared to the control group (95% CI, 1,36-6,97; p=0,006).Conclusion. The study of genetic factors in the development of pulmonary embolism (FGA, ITGA2, PAI-1) is necessary to create a personalized approach to patient management at all stages.